ASEAN dan Keselamatan Serantau - Azizah, Binti Baharudin (Universiti Malaysia Sarawak, (UNIMAS), 1997)
This study explores the role played by the Association of Southeast Asian Nations (ASEAN), a regional organization in South East Asia since it was first established. This study emphasizes the political aspect of ASEAN, especially its security aspect. Although the main objective of ASEAN is to enhance economic and socio-cultural, security, development and cooperation, remains an important factor in maintaining the stability of this region. This is important because the region is often in turmoil with confrontation occurring between countries; unresolved security issues as well as interference by foreign powers in the region. It is obvious that political growth ensures sound economic growth. Thus, this study evaluates the effectiveness of ASEAN in ensuring regional security. The present situation may change as ASEAN will soon expand to include 10 countries as members in near future. Nevertheless, the appearance of this single regional organization in South East Asia is seen as ensuring harmony and safety. This situations makes ASEAN one of the most successful regional organizations in the Third World.